New susceptibility locus for coronary artery disease on chromosome 3q22.3 - Erdmann, Jeanette; Großhennig, Anika; Braund, Peter S; König, Inke R; Hengstenberg, Christian; Hall, Alistair S; Linsel-Nitschke, Patrick; Kathiresan, Sekar; Wright, Ben; Trégouët, David-Alexandre; Cambien, Francois; Bruse, Petra; et al. (Nature genetics, 2009)
Jeanette Erdmann and colleagues identify a locus on chromosome 3q22.3 associated with coronary artery disease. The SNP with the strongest association is in MRAS , which encodes a membrane-anchored GTP-binding protein. We present a three-stage analysis of genome-wide SNP data in 1,222 German individuals with myocardial infarction and 1,298 controls, in silico replication in three additional genome-wide datasets of coronary artery disease (CAD) and subsequent replication in ∼25,000 subjects. We identified one new CAD risk locus on 3q22.3 in MRAS ( P = 7.44 × 10 −13 ; OR = 1.15, 95% CI = 1.11–1.19), and suggestive association with a locus on 12q24.31 near HNF1A-C12orf43 ( P = 4.81 × 10 −7 ; OR = 1.08, 95% CI = 1.05–1.11).